2020
DOI: 10.14814/phy2.14461
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet induced obesity and age influence the telomere shelterin complex and telomerase gene expression in mouse adipose tissue

Abstract: In the United States, the prevalence of obesity is increasing (Hales, Carroll, Fryar, & Ogden, 2017) alongside the number of elderly individuals (He, Goodking, & Kowal, 2016). Both obesity and aging are independent risk factors for many chronic diseases, including type 2 diabetes (Barnes, 2011;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Telomere shortening is associated with cardiovascular events, stroke, type 2 diabetes, and a higher mortality rate ( 10 ). Several lifestyle-related factors are associated with telomere shortening like smoking ( 11 – 13 ), alcohol intake even in minor amounts ( 14 , 15 ), low physical activity ( 16 , 17 ), and high-fat diets ( 18 , 19 ) that trigger telomere shortening. Obesity is a well-known risk factor for many age-related comorbidities and directly increases the risk of oxidative stress and inflammation ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Telomere shortening is associated with cardiovascular events, stroke, type 2 diabetes, and a higher mortality rate ( 10 ). Several lifestyle-related factors are associated with telomere shortening like smoking ( 11 – 13 ), alcohol intake even in minor amounts ( 14 , 15 ), low physical activity ( 16 , 17 ), and high-fat diets ( 18 , 19 ) that trigger telomere shortening. Obesity is a well-known risk factor for many age-related comorbidities and directly increases the risk of oxidative stress and inflammation ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animals were housed at the Skidmore College animal facility on a 12:12 light:dark cycle and had access to food and water ad libitum. After initial acclimatization (1 week), the mice were randomized into either a high‐fat diet (HFD; 60% kcal from fat) or a low‐fat diet (LFD; 10% kcal from fat) group and consumed their respective diet for 4.5 months (Test Diets; Bloom et al., 2020; Reynolds et al., 2019; Shortreed et al., 2009; Trajcevski et al., 2013). Using a randomized controlled design, during the final 8 weeks of the diet intervention, the groups were subsequently randomized to receive either vehicle (VEH, drinking water) or succinic acid (SA; 0.75 mg/ml in drinking water; Ferro, Carbone, Marzouk, et al., 2017; Ferro, Carbone, Zhang, et al., 2017; Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Upon the completion of the in vivo testing, mice were anesthetized with a 1:1:1 mixture of PromAce, ketamine hydrochloride, and xylazine by intraperitoneal injection (1.5 ml/ kg; Bloom et al, 2020 ). The soleus muscle, an oxidative skeletal muscle, was dissected and removed for subsequent determination of in vitro mitochondrial respiratory capacity.…”
Section: Tissue Harvestmentioning
confidence: 99%
“…Similarly, it has been observed that adiposity is associated with high plasma levels of lipoperoxidation due to an increase in 8-epi-prostaglandin F2α (8-epi-PGF2α), which leads to the appearance of complications, such as insulin resistance [ 220 ]. At the transcriptional level, it also has a negative impact, since it influences the gene expression of the shelterin complex, thereby altering the function of telomeres and triggering the inflammatory process and predisposition to chronic diseases [ 221 ].…”
Section: Components Of the Mets And Its Relationship With Oxidative Stress And Telomeric Lengthmentioning
confidence: 99%
“…In aged animals, TERT gene expression is negatively correlated with weight, while TNF-α and MCP-1 have a positive correlation, suggesting that age and weight are factors that impact telomerase expression. This can generate an alteration in the function of telomeres in adipose tissue, thereby predisposing to an inflammatory state and age-related chronic diseases [ 221 ].…”
Section: Telomere Length and Inflammation In The Metsmentioning
confidence: 99%